Catholic/Jesuit Values in an Introductory Religious Studies Course - Lynch, Patrick (Teaching theology and religion, 2012)
A growing interest in the communication to students of the mission and identity of a higher education institution prompted this study about the presence of Catholic, Jesuit values in the introductory religious studies course at a faith-based university. To conduct this study a survey instrument was developed, piloted, further refined, and then administered again to about four hundred and fifty students. The study's results showed that the introductory course had a positive effect on the majority of students surveyed, namely, those who had no Catholic schooling or only had a Catholic elementary school education. Statistically significant advances in several areas of knowledge about Catholic teachings endorsed by Catholic bishops and the pope occurred. Although less extensive, knowledge of Jesuit values also advanced in the course.